An Analytical Study of “Siah Ankh main Tasveer - Koukab, Farzana; Rani, Aasma; Naseem Sindhu, Aqsa (sourcecoder, 2022)
Although Mustansar Hussain Tarar became famous as a travel writer, he also holds a prominent position in the field of fiction due to his unique style and art. Fiction which is based on real events, political issues, history of Pakistan and true stories and psychological emotions makes it a unique contemporary fiction writer. The "Siah Ankh Mein Tasveer" myths make it clear that Mustansar Hussain Tarar not only felt the pain of Pakistan and its people but was also a part of it. In order to expose the political situation in these fictions, they have adopted a symbolic style and adapt the language and expression according to the lifestyle and circumstances of the characters. It would not be wrong to say that Mustansar Hussain Tarar works hard, responsibly and with love.